Modeling Ribavirin‐Induced Anemia in Patients with Chronic Hepatitis C Virus - LS Wu; LC Jimmerson; CE MacBrayne; JJ Kiser; DZ D'Argenio (CPT: Pharmacometrics & Systems Pharmacology)
Ribavirin remains an important component of hepatitis C treatment in certain clinical scenarios, but it causes hemolytic anemia. A quantitative understanding of the ribavirin exposure‐anemia relationship is important in dose individualization/optimization. We developed a model relating ribavirin triphosphate (RTP) exposure in red blood cells (RBCs), RBC lifespan, feedback regulation of RBC production when anemia occurs, and the resulting hemoglobin decline. Inosine triphosphatase (ITPA) and interleukin 28B (IL28B) genetics were found to be significant covariates. Clinical trial simulations predicted that anemia is least severe in IL28B non‐CC (rs12979860, CT or TT), ITPA variant subjects, followed by IL28B non‐CC, ITPA wild‐type, IL28B CC, ITPA variant, and IL28B CC, ITPA wild‐type subjects (most severe). Reducing the ribavirin dose from 1,200/1,000 mg to 800/600 mg could reduce the proportions of grade 2 anemia by about half. The resulting model framework will aid the development of dosing strategies that minimize the incidence of anemia in treatment regimens that include ribavirin.